Comparative evaluation of efficacy of manual vis-à-vis automated colony counting techniques used for enumeration of microorganisms in meat - Karabasanavar, Nagappa S.; Shetty, Krithi; Hegde, Naveen; Zende , R.J. (Journal of Meat Science, 2012)
Manual counting of colony forming units (CFU) grown over a semi-solid media is a tedious process while enumerating microorganisms in foods such as meat and meat products thereby necessitating automation. In the present study, automated colony counter was validated against manual colony counting by counting CFUs grown on solid agar plates. Colonies grown on agar medium by standard plate count technique of meat samples were enumerated by both counting methods. Upon counting colonies in the range of 10-1000 per plate, it was found that the values of automated counting were on par with the manual counting as revealed by linear eqnation (y = 1.0011x + 0.588, R2 = 0.9998). Keeping in view the time consumption and tedious effort exercised during manual counting of colonies on solid media, automated counting technique using imaging technology was found rapid, accurate and convenient.
Keywords: Colony count; CFU; enumeration; imaging